Hemolytic disease of the newborn caused by anti-U: A case report - Renata Esteves Almeida; Sandro Artur Fierz; Flavia Miranda Constantino-Bandeira; Patricia Olga Souza-Sergio; Cristiane Sá Ferreira Facio; Alexandre Gomes Vizzoni (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Maternal red blood cell alloimmunization is an important cause of morbidity and mortality in the antepartum and neonatal periods. Typically, the serological diagnosis of Hemolytic Disease of the Fetus and Newborn (HDFN) includes a positive direct antiglobulin test on the infant's red blood cells and the presence of an IgG red cell alloantibody in both maternal and cord sera.